Housing Policy in Uzbekistan During the Years of Independence (On the Basis of Normative Legal Acts) - Matyakubov Nurbek (Zien Journals, 2021)
The radical reforms implemented in Uzbekistan in recent years are laying the foundation for the development of socio-economic and cultural life of the country. In this process, special attention will be paid to the state support of the housing sector, the development of industrial enterprises producing construction materials, providing the population with quality and affordable housing that meets local conditions and state support for enterprises specializing in the development of construction materials. In particular, as a result of increasing attention to housing policy in recent years, housing construction in cities and villages has expanded. This situation is helping to meet the demand for housing
Keywords: Construction materials; individual and cooperative housing; service apartment; housing policy